Holding the Inflammatory System in Check: TLRs and Their Targeted Therapy in Asthma - Zhiyong Dong; Lingxin Xiong; Weijie Zhang; Peter G. Gibson; Ting Wang; Yanjiao Lu; Guoqiang Wang; Hui Li; Fang Wang (Mediators of Inflammation)
Inflammation is a complex biological response to detrimental stimuli and can be a double-edged sword. Inflammation plays a protective role in removing pathogenic factors, but dysregulated inflammation is associated with several major fatal diseases such as asthma, cancer, and cardiovascular diseases. Asthma is a complex heterogenous disease caused by genetic and environmental factors. TLRs are the primary proteins associated with the innate and adaptive immune responses to these fatal factors and play an important role in recognizing pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), which initiates the downstream immune response. Due to the complex TLRs cascade and nowadays unsuccessful control in asthma, new studies are focused on TLRs and other potential targets in TLR cascade to minimize airway inflammation.